L.N Tolstoy and A. Yeniki: Concept of Personality and Peculiarities of their Artistic Embodiments. - FAKHRUTDINOVA, LILIYA ILDAROVNA; RUDALEVNA AMINEVA, VENERA; SIBGATULLINA, ALFINA TAGIROVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Contact ties and typological convergence between the work of Tolstoy and Yeniki and russian writers of 19-20th centuries attracted the attention of some scientists. It is attempted to understand the writer’s concept of personality and his/her artistic representation as a focus of national identity literature for the first time in this work. The concept of the study was shaped by the differences between personality and character established in literature. The results of the study are important for understanding the content and characteristics of the functioning of categories universal and unique in the cross-literary process. RESUMEN Los lazos de contacto y la convergencia tipológica entre el trabajo de Tolstoy y Yeniki y los escritores rusos de los siglos XIX y XX atrajeron la atención de algunos científicos. Se intenta entender el concepto de personalidad del escritor y su representación artística como foco de la literatura de identidad nacional por primera vez en este trabajo. El concepto del estudio fue moldeado por las diferencias entre personalidad y carácter establecidas en la literatura. Los resultados del estudio son importantes para comprender el contenido y las características del funcionamiento de las categorías universales y únicas en el proceso trans-literario.